Application of TiCN on passively harmonic mode-locked ultrashort pulse generation at 2 µm. (June 2022) - Ma, Xiaohui; Liu, Shaoqing; Dai, Wenwen; Chen, Wu; Tong, Liang; Ye, Shanshan; Zheng, Ziqi; Wang, Yangyang; Zhou, Yong; Zhang, Wei; Fang, Wentan; Chen, Xiaolin; et al.
Highlights: TiCN saturable absorber was applied in mode-locking for the first time. 2 μm harmonic mode-locking from the 2nd to the 16th order. The maximum pulse repetition rate of 444.10 MHz that has ever been demonstrated in a TiCN-based fiber laser. Abstract: TiCN could be a promising optical switch for the generation of ultrashort pulses with high repetition rates. Harmonic mode-locking (HML) is realized in a thulium-doped fiber laser (TDFL) using titanium carbonitride (TiCN) as a saturable absorber (SA). The linear absorption of TiCN is about 50% at 1950 nm, while the nonlinear modulation depth and saturation power are 6.76% and 1.83 kW, respectively. The fundamentally mode-locked pulses have the central wavelength of 1949.60 nm, 3-dB bandwidth of 5.20 nm, repetition rate of 27.73 MHz, and pulse width of 790 fs. The 2nd to the 16th harmonics are observed, corresponding to the repetition rates ranging from 55.44 to 444.10 MHz. To the best of our knowledge, this is the highest operating frequency in TiCN-based fiber laser. The central wavelength, 3-dB bandwidth, and pulse width are investigated as a function of harmonic order. This work would advise a new application area for TiCN.